Etika Pemanfaatan Energi dalam Perspektif Al-Qur’an dan As-Sunnah - Udin Saprudin (Lembaga Yasin AlSys, 2026)
The issue of sustainable energy use has been widely discussed in environmental and global ethics studies; however, scholarship that specifically examines the ethical foundations of energy use from the perspectives of the Qur’an and As-Sunnah remains relatively limited and has not yet been systematically integrated. This study aimed to analyze the principles of energy-use ethics in Islam and their implications for human behavior and energy resource management policies. The study employed a qualitative approach with a library research design, drawing data from primary sources in the form of relevant Qur’anic verses and Prophetic hadith, as well as secondary sources including tafsir works, hadith commentaries, and contemporary scholarly literature addressing environmental and energy ethics. Data were analyzed using thematic and hermeneutic analysis to trace the normative and contextual meanings of religious texts. The findings indicate that the Qur’an and As-Sunnah emphasize the principles of amanah, justice, balance (mīzān), the prohibition of isrāf (wastefulness), and responsibility as khalifah in energy use. These findings contribute to the development of an energy ethics framework grounded in Islamic values and broaden understanding of the relationship between religious teachings and sustainability issues. The study concludes that internalizing Islamic ethical values in energy governance plays an important role in promoting just and sustainable energy use; therefore, governments, educational institutions, and policy stakeholders need to integrate these principles into energy policy formulation. The implications include a theoretical contribution to the development of Islamic ethics and environmental studies, practical implications for value-based sustainable development, and openings for further research on implementing Islamic energy ethics in public policy and modern industrial practice.